JURIDIC CONSEQUENCES OF CANCELLATION OF FLIGHT DEPARTURE BY PT. GARUDA INDONESIA LINKED TO LAW NUMBER 1 YEAR 2009 CONCERNING JO. LAW NUMBER 8 OF 1999 CONCERNING CONSUMER PROTECTION - Nurhadi Purnomo (Fox Justi : Jurnal Ilmu Hukum, 2020)
People in the modern era today in their activities are required to have high mobility. Airplanes are an alternative to meet these needs, because they have a wide range and fast travel time. In the last 10 years, airline companies have mushroomed rapidly and provided positive implications for the community, but on the other hand, they have created competition by impacting on cheap tickets with less than excellent service. The company prioritizes profits without taking into account risks. Flight cancellation is one of the problems that often arise from airlines. This has legal consequences related to consumer protection. PT. Garuda Indonesia in 2015 has canceled flights. This needs to be studied with a descriptive analytical research method with a normative juridical approach and the data analyzed qualitatively. Research on the legal consequences of cancellation of flight departures by PT. Garuda Indonesia is linked with Law No. 1 of 2009 concerning Flight Jo. Law Number 8 of 1999 concerning Consumer Protection states that; the first which is often a factor in the cancellation of PT. Garuda Indonesia is the weather factor, human error factor and natural disaster factor; second, the responsibility of PT. Garuda Indonesia against departure cancellations is by returning airplane tickets for passengers who will not continue their journey, giving exchanges for other airline tickets with the same price and destination, delaying departure at another time with the facilitation of free lodging and meals that have been provided by PT. Garuda Indonesia; third, the effort that can be made by consumers due to flight cancellations is to claim compensation from PT. Garuda Indonesia by proving and showing tickets or air cargo letters.